Caenocholax fenyesi (Strepsiptera: Myrmecolacidae) parasitic in Camponotus planatus (Hymenoptera: Formicidae) in Mexico: Is this the original host? - Kathirithamby, J; Hughes, D (Oxford University Press, 2002)
The male of Caenocholax fenyesi Pierce (Strepsiptera) is widespread in South America, but no host records are known as the specimens examined were free-living males that came into traps. In southern USA C. fenyesi was found to parasitize the red imported fire ant, Solenopsis wagneri Santschi (Hymenoptera: Formicidae). We found a nest of the carpenter ant, Camponotus planatus Roger, in Veracruz, Mexico to be parasitized by C. fenyesi. This is the first record of a host of C. fenyesi from the Neotropics. At the same location Pierce (1909) found the type species of C. fenyesi, but there were no host records. As our findings were from the same location, we speculate whether C. planatus is the endemic host of C. fenyesi. If so, did C. fenyesi arrive in southern USA parasitic on C. planatus, and move to an exotic host, S. wagneri in an alien enviroment? We also synonomize Myrmecolax ogloblini Luna de Carvalho and Caenocholax brasiliensis Oliveira & Kogan from Brazil with C. fenyesi, based on the unique structure of the aedeagus of the latter.